The Relation of Immunity Reactions to the Biogenetic Law: Investigations of the Chemical Structure of the Protoplasm of Animals during Embryonic Development by Means of Heterogeneous Hemolysins - Kritchevsky, I. L. (The Journal of infectious diseases, 1923)
The hen's egg and the formative yolk do not contain heterogeneous sheep antigen. In earlier phases of the development (2 days), the protoplasm of the hen embryo does not possess heterogeneous sheep antigen. The heterogeneous sheep antigen producing hemolysins against red corpuscles of sheep appears only in relatively advanced periods of the development of the hen; that is, not before 4 days after the division of the egg began. Therefore we can state that the biochemical properties of animal cells are subject to transformation during the ontogenetic development.